Computational Geometry-Based 3D Yarn Path Modeling of Wound SiCf/SiC-Cladding Tubes and Its Application to Meso-Scale Finite Element Model - Tang, Jianbo; Zhao, Gang; Wang, Jun; Ding, Yue; Feng, Yajie; Chen, Yunsheng; Zhang, Chao; Huang, Qing; Xin, Shiqing; Xu, Jian (Frontiers in Materials, 2021)
The filament winding process is a competitive performing technology for nuclear fuel cladding tubes due to its high automation. The study of the yarn path on the mandrel surface is vital to design and produce the cladding tube with the desired mechanical properties, reducing manufacturing time and costs. The geodesic and semi-geodesic trajectories are used to create a 3D yarn path in this paper. A 3D yarn path optimization method based on the principle of minimum potential energy is proposed to simulate the overlap effect in accord with the real winding process. The finite element (FE) mesh based on the 3D yarn path has been used for the mechanical analysis of the cladding tube. The embedded region constraint is applied to define the interaction between the matrix mesh and the yarn mesh to model the meso-structure of the cladding tube. Based on the meso-scale FE model, the mechanical behavior of the wound SiCf/SiC nuclear fuel cladding tube is studied in detail. The results show that due to the neglect of the overlap effect, the conventional laminate model overestimates the cladding tube strength. The proposed meso-scale FE model can accurately predict the failure of the cladding tube. The results also confirm that the creation of a 3D yarn path and the derived meso-scale FE model, representing an accurate wound structure, are of importance to the prediction of the performance of the cladding tube.